The Role of information technology (IT) in innovation performance Institute for the Intellectual Development of Children and Young Adults - Yousef Mohammadi moghaddam; Javad Madani; Masumeh Pahlevani Qummi (مطالعات مدیریت کسب و کار هوشمند, 2014)
With the advent of the era of information technology, significant developments in today's society has been created which extensive changes in communities and organizations have been caused. One of the most important issues facing the organization, the concept of innovation and its related concepts. Innovation as a vital and effective role to help today's organizations by the organization to better performance and gain competitive advantage. The most important tools in current era is information technology applications and unique benefits to organizations created. The main objective of this study is to investigate the role of IT in innovation pe  rformance and the IT component of an effective role in enhancing the innovative performance of the organization. The research method is descriptive – survey. The Statistical Society included 86 employees of the Institute for the Intellectual Development of Children and Young Adults in Tehran (Central Intelligence Agency) is to collect information, Information technology and innovation performance of the questionnaire with the whole five-item Likert used. Validity of the questionnaire was confirmed by a number of experts and specialists in management, then to assess the reliability, Cronbach's alpha coefficient was used for the first and second questionnaire, respectively 905. 848. And that was the right amount. Using the software Spss and Lisrel the tests were conducted on the data. The results showed that IT positive impact on innovation performance has a direct and significant and can have an effective role in enhancing the innovative performance.